Investigating the impact of Shari'ah perception on customer switching intentions: A study of Takāful and conventional insurance - Hassan Jamil; Waheed Akhter (Cogent Business & Management, 2016)
The core objective of this paper is to examine the relationship between the Shari'ah perceptions and the customers' switching intentions in both Takāful and Conventional Insurance. In today's world, most of the businesses are focusing on customer retention rather than the customer acquisition. However, our current knowledge of insurance systems is unable to address the crucial issues of target achieving marketing tactics. Takāful is firming its roots in Muslim communities across the globe. As per customer satisfaction been considered as an important factor of customer switching, we have gone further and investigated the mediating role of customer satisfaction to customer switching intentions. The sample size of 400 customers of major life Insurance and family Takāful companies was taken using convenient sampling method. Mediation analysis was performed to test the mediating role of customer satisfaction in Family Takāful and Life Insurance. The impact of Shari'ah perceptions in life insurance and family Takāful was found significant. Furthermore, customer switching intentions were partially mediated by customer satisfaction. This study has some important implications for the insurance/Takāful practitioners and policymakers. It urges the Insurance/Takāful operators to maintain and develop strong long-term relationships with the customers to reduce their switching intentions. For Takāful practitioners, there is a need to develop clear understanding of Takāful in the minds of customers as well as general public.
Keywords: 650